A STUDY OF ARTIFICIAL INTELLIGENCE ON THE IMPACTS OF VIRTUAL ASSISTANTS ON COMPANIES - Martins, Taina Almeida; Sanchez, Christiane Ratton; Araújo, Liriane Soares (Revista Interface Tecnológica, 2022)
This work aims to present a study on Artificial Intelligence, focusing on the impacts of virtual Assistants in Companies to identify new functionalities and ways of business functioning, helping both in the implementation for companies and in the use by end users Virtual Assistants are software used to serve customers in the form of a robot, which has pre-programmed functions and also features that allow for learning. This technology can bring benefits, but also challenges and disadvantages due to the loss of direct contact with a human being. The research methodology involves descriptive and exploratory bibliographic and documentary analysis with a qualitative approach of an applied nature, as well as a survey through cases found on the internet. It is expected to help in the literature, considering that it is a new topic, as well as to help companies in the choice of use.